The Effect of Glycerol Supplements on Aerobic and Anaerobic Performance of Athletes and Sedentary Subjects - Patlar, Suleyman (Akademia Wychowania Fizycznego w Katowicach, 2012)
The purpose of this study was to evaluate the effect of glycerol supplementation on aerobic and anaerobic exercise performance in sedentary subjects and athletes. The glycerol supplement treatments were as follows: 40 volunteers were selected and divided into two groups, sedentary and exercise groups. These two groups were further subdivided into two groups. The first group, the placebo (S), only consumed water; the second group (GS) consumed glycerol followed by water. Neither of these groups did any exercise for 20 days. The third and fourth groups consisted of the exercise group subjects; they were required to perform a 20-m shuttle run test every day for 20 days. The third group’s subjects, the placebo (E), only consumed water. The last group (GE) consumed glycerol followed by water. The Astrand Cycle Ergometer Test (ACET) was performed, and the Cosmed K4b(2) portable gas analysis system was used to determine the aerobic capacity, while the Wingate Anaerobic Power Test (WAPT) was performed to determine the level of anaerobic power. The 20 Meter Shuttle Run Test (20MSRT) was performed after glycerol supplementation throughout the 20 days, and the exercise periods and distances were recorded. The glycerol supplement was found to have an increasing effect on aerobic and anaerobic performance in GS, E and GE. A similar effect was found for the covered distances and time in the same groups. However, an adverse effect was found on body weight.